MYXEDEMA ASCITES: A RARE INITIAL PRESENTATION OF HASHIMOTO THYROIDITIS - Vimalanathan, Sanmuga; Mugilarassan, Sivasangkari (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Ascites due to hypothyroidism is rare and only occurs in less than 4% of cases. Here, we present a case of severe hypothyroidism due to Hashimoto’s thyroiditis, where the patient’s initial presentation was gross ascites. CASE A 45-year- old male who has hypertension, presented with worsening abdominal distension for 1 month. Examination showed gross ascites and bilateral lower limb oedema with no other stigmata of chronic liver disease. Peritoneal fluid Serum-Ascites Albumin Gradient (SAAG) was 0.5 g/dL, suggesting a non-portal hypertension cause of ascites with high protein level of 2.9 g/dL and presence of lymphocytes count of 30 cell/mm3. Peritoneal fluid examination, imaging and endoscopy findings excluded the usual causes of ascites. Patient showed no response to initial treatment with diuretics and required multiple abdominal paracentesis. Echocardiogram showed presence of loculated pericardial effusion at posterior wall measuring 1.15 - 1.44 cm. Thyroid function test (TFT) was then done, showed severe hypothyroidism (Free T4 <5.41 pmol/L and TSH 89.71 mIU/L) secondary to Hashimoto’s thyroiditis (anti-TPO 205 IU/mL). Patient was started on L-Thyroxine 150 mcg OD. There was significant resolution of ascites with normalisation of TFT. It was postulated that low level of T3, increases level of Hyaluronic acid (HA), HA then induces capillary leak which results in fluid accumulation. Literature suggests that in patients with ascites who have SAAG less than 1.1 g/dL, high protein level (>2.5 g/dL), and predominant cell count of lymphocytes, hypothyroidism should be suspected. Early suspicion of hypothyroidism prevents patients from undergoing unnecessary procedures while its treatment provides resolution of ascites. CONCLUSION Hypothyroidism should be considered in patients with unexplained cause of ascites